Strengthening the emergency referral system in Cambodia for women and children under five: a description of interventions and impact analysis - Peter C Acker; Loretta N Matheson; Tuon Sovanna; Dim Sophearom; Matthew C Strehlow (Inishmore Laser Scientific Publishing Ltd, 2019)
# Background Many factors align to reduce access to quality emergency services in Cambodia, resulting in unnecessary morbidity and mortality among the country's most vulnerable populations. The lack of a well-coordinated emergency referral system acts as a critical barrier for many seeking emergency care, limiting overall referral frequency and quality. To increase the effectiveness of the Cambodian healthcare system, the Quality Health Services (QHS) project implemented a spectrum of targeted, low-cost, locally-tailored interventions, including: triage systems, provincial clinical guidelines and referral hotlines, standardized referral-communication slips, and referral-feedback forms. To inform future health-system-strengthening efforts, the primary aim of this study is to describe the challenges facing the Cambodian referral system and the interventions applied to address these challenges. Secondarily, this study aims to characterize the frequency of emergency referrals in the post-intervention period and the utilization patterns of the implemented referral-system-strengthening tools. # Methods Data was collected prospectively on a quarterly basis at 35 government referral hospitals in six Cambodian provinces between March 2016 and June 2017, data from 25 of these facilities was analyzed. Data on overall numbers of referrals was collected from each facility's referral logbook. The frequency and thoroughness of standardized referral-communication slip and standardized referral-feedback form use was ascertained by reviewing copies of these tools collected at each facility during the preceding quarter. # Results The average number of emergency referrals to target facilities increased from 114.4 to 190.4 per quarter, a 66% increase. Target facilities also received 86% more standardized referral-communication slips and sent 200% more standardized referral-feedback forms per quarter during the monitoring period. # Conclusions After receiving a package of referral-system-strengthening interventions the 25 hospitals analyzed in this study noted a significant increase in the frequency of emergency referral receipt. The frequency and quality of referral related communication improved consistently during the observation period as well. This data suggests that the interventions implemented addressed ongoing gaps in the Cambodian health system, and improved access to emergency referrals. These developments create a foundation upon which to build future health system strengthening interventions can be built and may provide guidance to implementors in other similarly resourced settings.